2/9m=6

23 answers

To solve for m, we can multiply both sides of the equation by 9 to get rid of the fraction:

2/9m * 9 = 6 * 9

This simplifies to:

2m = 54

To isolate m, we can divide both sides of the equation by 2:

2m/2 = 54/2

m = 27
23=x/6+2
To solve for x, we can start by subtracting 2 from both sides of the equation:

23 - 2 = x/6 + 2 - 2

This simplifies to:

21 = x/6

To isolate x, we can multiply both sides of the equation by 6:

6 * 21 = 6 * (x/6)

This simplifies to:

126 = x

So, x = 126
k-9/2=10
To solve for k, we can start by adding 9/2 to both sides of the equation:

k - 9/2 + 9/2 = 10 + 9/2

This simplifies to:

k = 10 + 9/2

To add the fractions, we need a common denominator, which is 2:

k = 10 * 2/2 + 9/2

This simplifies to:

k = 20/2 + 9/2

Combining the numerators:

k = (20 + 9) / 2

Simplifying further:

k = 29/2

So, k = 29/2 or k = 14.5
k-5/4=12
To solve for k, we can start by adding 5/4 to both sides of the equation:

k - 5/4 + 5/4 = 12 + 5/4

This simplifies to:

k = 12 + 5/4

To add the fractions, we need a common denominator, which is 4:

k = 12 * 4/4 + 5/4

This simplifies to:

k = 48/4 + 5/4

Combining the numerators:

k = (48 + 5) / 4

Simplifying further:

k = 53/4

So, k = 53/4 or k = 13.25
-2(r+8)=-27
To solve for r, we can start by distributing the -2 to both terms inside the parentheses:

-2(r + 8) = -27

-2r - 16 = -27

Next, we can add 16 to both sides of the equation to isolate the term with r:

-2r - 16 + 16 = -27 + 16

-2r = -11

To solve for r, we can divide both sides of the equation by -2:

-2r / -2 = -11 / -2

r = 11/2 or r = 5.5
8n-(5n+4)=11
To solve for n, we can start by simplifying the equation:

8n - (5n + 4) = 11

First, we can distribute the negative sign to the terms inside the parentheses:

8n - 5n - 4 = 11

Combine like terms:

(8n - 5n) - 4 = 11

3n - 4 = 11

Next, we can isolate the term with n by adding 4 to both sides of the equation:

3n - 4 + 4 = 11 + 4

3n = 15

Finally, we can solve for n by dividing both sides of the equation by 3:

3n/3 = 15/3

n = 5
Angie and Kenny play online video games. Angie buys 1 software package and 2 months of game play. kenny buys 1 software package and 4 months of game play each software package cost $25 if their total cost is 170 what is the cost of one month of game play
Let's denote the cost of one month of game play as "x".

According to the given information, Angie buys 1 software package and 2 months of game play, so her cost would be:

1 * $25 (software package) + 2 * x (2 months of game play) = $25 + 2x

Similarly, Kenny buys 1 software package and 4 months of game play, so his cost would be:

1 * $25 (software package) + 4 * x (4 months of game play) = $25 + 4x

Since their total cost is $170, we can form an equation:

$25 + 2x + $25 + 4x = $170

Combining like terms:

$50 + 6x = $170

To isolate the variable, we can subtract $50 from both sides of the equation:

$50 + 6x - $50 = $170 - $50

6x = $120

Finally, we can solve for x by dividing both sides of the equation by 6:

6x / 6 = $120 / 6

x = $20

Therefore, the cost of one month of game play is $20.
5g+2(-7+4g)=1-g
Let's simplify the equation step by step:

5g + 2(-7 + 4g) = 1 - g

First, we simplify the expression inside the parentheses:

5g - 14 + 8g = 1 - g

Next, we combine like terms on both sides of the equation:

13g - 14 = 1 - g

To isolate the variable terms, we can add g to both sides and add 14 to both sides:

13g + g - 14 + 14 = 1 - g + g + 14

This simplifies to:

14g = 15

Finally, we solve for g by dividing both sides of the equation by 14:

14g / 14 = 15 / 14

g = 15/14

Thus, the solution is g = 15/14 or approximately g = 1.07.
-2(-c-16)=-2c-16
To simplify the equation, we can start by distributing the -2 to the terms inside the parentheses:

-2(-c - 16) = -2c - 16

Next, we can simplify each side of the equation:

2c + 32 = -2c - 16

Now, we can isolate the variable by adding 2c to both sides and then subtracting 32 from both sides:

2c + 2c + 32 = -2c + 2c - 16 - 32

4c + 32 = -16

Then, we can subtract 32 from both sides:

4c + 32 - 32 = -16 - 32

4c = -48

Finally, we solve for c by dividing both sides by 4:

4c/4 = -48/4

c = -12

Thus, the solution is c = -12.
A=P+PRT for T
To solve for T, we can start by isolating the variable on one side of the equation.

A = P + PRT

We can move P to the other side by subtracting P from both sides:

A - P = PRT

Next, we can divide both sides of the equation by PR to solve for T:

(A - P) / (PR) = T

So, T = (A - P) / (PR)
A rectangle has perimeter 54 cm and the lenght 22 cm what is its width
To find the width of the rectangle, we first need to understand the formula for the perimeter of a rectangle:

Perimeter = 2(length + width)

Given the information that the perimeter is 54 cm and the length is 22 cm, we can substitute these values into the formula:

54 = 2(22 + width)

Next, we simplify the equation by combining like terms:

54 = 44 + 2(width)

To isolate the variable, we subtract 44 from both sides:

54 - 44 = 44 + 2(width) - 44

10 = 2(width)

Finally, we solve for the width by dividing both sides by 2:

10/2 = 2(width)/2

5 = width

Therefore, the width of the rectangle is 5 cm.
-8=5x-3
To solve for x, we can start by isolating the variable on one side of the equation.

-8 = 5x - 3

To isolate the term with x, we can add 3 to both sides of the equation:

-8 + 3 = 5x - 3 + 3

-5 = 5x

Next, we can solve for x by dividing both sides of the equation by 5:

-5/5 = 5x/5

-1 = x

Thus, the solution is x = -1.